2014
DOI: 10.1002/cam4.271
|View full text |Cite
|
Sign up to set email alerts
|

CT versus FDG‐PET/CT response evaluation in patients with metastatic colorectal cancer treated with irinotecan and cetuximab

Abstract: We compared morphologic computed tomography (CT)-based to metabolic fluoro-deoxy-glucose (FDG) positron emission tomography (PET)/CT-based response evaluation in patients with metastatic colorectal cancer and correlated the findings with survival and KRAS status. From 2006 to 2009, patients were included in a phase II trial and treated with cetuximab and irinotecan every second week. They underwent FDG-PET/CT examination at baseline and after every fourth treatment cycle. Response evaluation was performed pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…So far, however, there only relatively few and mostly small studies comparing RECIST and PERCIST (References: [17] [42] [43] [44] [45] [46] [47] [48] [20] [49] [50] [51] [21] [52] [53] [24] [23] [25] [54] [26] [55] [56]). A meta-analysis published in 2016 identified 6 studies including 268 patients [57].…”
Section: Limitations Of Recist and Opportunities For Fdg Pet Based Rementioning
confidence: 99%
“…So far, however, there only relatively few and mostly small studies comparing RECIST and PERCIST (References: [17] [42] [43] [44] [45] [46] [47] [48] [20] [49] [50] [51] [21] [52] [53] [24] [23] [25] [54] [26] [55] [56]). A meta-analysis published in 2016 identified 6 studies including 268 patients [57].…”
Section: Limitations Of Recist and Opportunities For Fdg Pet Based Rementioning
confidence: 99%
“…Several studies have previously reported the ability of FDG-PET/CT to predict outcomes in patients undergoing treatment for mRCC [12][13][14][23][24][25][26][27][28][29], but the methodologies between these studies were variable limiting overall conclusions. Our study used PERCIST which provides greater detail on lesion analysis and may be less ambiguous [18] than other PET based criteria [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The most common evaluation of a certain therapy to cancer is based on the initial diagnosis of TNM stage, which may reveal the current status and might predict the therapeutic outcome [27]. However, the morphologic and metabolic responses of cancer cells to a specific treatment are incongruent.…”
Section: Monitoring Efficacy Of Treatmentsmentioning
confidence: 99%
“…However, the morphologic and metabolic responses of cancer cells to a specific treatment are incongruent. For example, cetuximab and other targeted therapies inhibit cancer cell growth by inhibiting the proliferation, angiogenesis, and metastatic spread and by promoting apoptosis [28][29][30], which should be cytostatic rather than cytotoxic [27]. However, in many cases, especially in the early-phase post-therapy, the change of cellular or biochemical function may be significant, but a measurable reduction in tumor size may not occur.…”
Section: Monitoring Efficacy Of Treatmentsmentioning
confidence: 99%